Transcription of the E2F-1 gene is rendered cell cycle dependent by E2F DNA-binding sites within its promoter. - Neuman, E (1994)
The cell cycle-regulatory transcription factor E2F-1 is regulated by interactions with proteins such as the retinoblastoma gene product and by cell cycle-dependent alterations in E2F-1 mRNA abundance. To better understand this latter phenomenon, we have isolated the human E2F-1 promoter. The human E2F-1 promoter, fused to a luciferase cDNA, gave rise to cell cycle-dependent luciferase activity upon transfection into mammalian cells in a manner which paralleled previously reported changes in E2F-1 mRNA abundance. The E2F-1 promoter contains four potential E2F-binding sites organized as two imperfect palindromes. Gel shift and transactivation studies suggested that these sites can bind to E2F in vitro and in vivo. Mutation of the two E2F palindromes abolished the cell cycle dependence of the E2F-1 promoter. Thus, E2F-1 appears to be regulated at the level of transcription, and this regulation is due, at least in part, to binding of one or more E2F family members to the E2F-1 promoter.